1992
DOI: 10.1037/0278-6133.11.4.250
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of behavioral treatment for chemotherapy-induced nausea and vomiting when administered by oncologists, oncology nurses, and clinical psychologists.

Abstract: Adequate control of side effects during medical treatment of cancer increases patient compliance and quality of life. Antiemetic drugs are not an effective treatment for the one in three cancer patients on chemotherapy who experience anticipatory nausea and vomiting (ANV); the behavioral treatment of systematic desensitization has been found effective for ANV when delivered by clinical psychologists. This study examined the effectiveness of systematic desensitization when delivered by medical personnel versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…58,64 Patients who receive a combined intervention of relaxation plus guided imagery have a reduced incidence of nausea during chemotherapy, lower incidence, duration, and severity of post-chemotherapy nausea, shorter duration of post-treatment vomiting, 65,66 and a more positive experience with chemotherapy than patients who receive antiemetic treatment alone. 67 Other interventions include hypnosis, or suggestive therapy [68][69][70][71] systematic desensitization 72 biofeedback, 56 wristbands, 73 and electrical stimulation at the wrist. 74 No single mode of delivery of these behavioral interventions is universally effective or flawless.…”
Section: Induced Nausea and Vomitingmentioning
confidence: 99%
“…58,64 Patients who receive a combined intervention of relaxation plus guided imagery have a reduced incidence of nausea during chemotherapy, lower incidence, duration, and severity of post-chemotherapy nausea, shorter duration of post-treatment vomiting, 65,66 and a more positive experience with chemotherapy than patients who receive antiemetic treatment alone. 67 Other interventions include hypnosis, or suggestive therapy [68][69][70][71] systematic desensitization 72 biofeedback, 56 wristbands, 73 and electrical stimulation at the wrist. 74 No single mode of delivery of these behavioral interventions is universally effective or flawless.…”
Section: Induced Nausea and Vomitingmentioning
confidence: 99%
“…7,8 Early studies in this area focused on the use of psychosocial interventions to improve quality of life among chemotherapy patients who had developed anticipatory nausea and vomiting. This research demonstrated that a variety of professionally administered interventions, including progressive muscle relaxation training with guided imagery, 9,10 systematic desensitization, 11 and biofeedback, 12 were effective in relieving nausea, vomiting, and emotional distress in the period just before chemotherapy administration. Some of the same interventions were also found to have beneficial effects on nausea, vomiting, and emotional distress in the hours and days after chemotherapy administration.…”
mentioning
confidence: 99%
“…Some of the same interventions were also found to have beneficial effects on nausea, vomiting, and emotional distress in the hours and days after chemotherapy administration. 10,11 These studies encouraged further research that has proceeded in two directions. One direction has involved modifying the delivery of the interventions so that they might become more accessible to chemotherapy patients experiencing aversive treatment side effects.…”
mentioning
confidence: 99%
“…Findings from previous studies have demonstrated that professionally administered interventions including guided imagery (Burish & Lyles, 1981;Lyles, Burish, Krozely, & Oldham, 1982), systematic desensitization (Morrow, 1986), and biofeedback (Burish & Jenkins, 1992) have been consistently effective in reducing nausea, vomiting, and emotional distress following chemotherapy. Similarly, self-administered psychological interventions have been shown to improve QOL, reduce psychological distress related to other clinical conditions (e.g., migraine headache) (McGrath et al, Self-Administered Stress Management Therapy 59 1992), and reduce cancer-related side effects (Morrow et al, 1992;Wilson, Taliaferro, & Jacobsen, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Morrow et al (1992) developed a behavioral treatment for chemotherapy-induced nausea and vomiting that could be delivered by oncologists and oncology nurses and compared its efficacy to the same treatment delivered by a professional psychologist or a no intervention control group. Interventions delivered by oncology professionals were found to be as effective as psychologists and superior to no intervention in relieving anticipatory nausea, anticipatory vomiting, and posttreatment nausea.…”
Section: Introductionmentioning
confidence: 99%